2022
DOI: 10.1177/0739456x221084992
|View full text |Cite
|
Sign up to set email alerts
|

Distance Teaching Urban Design and Planning Studio Courses during the Pandemic: Challenges and Lessons Learnt

Abstract: Urban design and planning studios presented considerable challenges to teach remotely following the outbreak of COVID-19 pandemic. Planning is space-based and requires real-life experience, and existing virtual teaching platforms can hardly re-create the studio atmosphere. This paper presents an empirical study, via surveys and interviews, on how instructors in Greek universities, where online teaching carried on for three semesters, adjusted studio courses to remote teaching. Findings are organized into three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…This points perhaps to an emergent studio culture in which students are willing to engage more independently with lecture material and for this engagement to develop in the expanded context of individual circumstance rather than in the 'flattened' environment of the classroom. This finding is consistent with recent studies (Fleischmann, 2021) which have broadly indicated a preference for hybrid design studios that utilise a virtual educational environment to transcend the geographical constraints of the university and broaden possible inputs, and also integrate the specific FTF needs of studiobased education (Mironowicz & Schretzenmayr, 2020;Katsavounidou, 2022). The clear preference for FTF presentations and reviews from both students and tutors shows that at the critical momentsthat is in the scenarios that may have a tangible impact on student progression and potential employabilitythere's no substitute for FTF studio.…”
Section: The Inevitability Of Hybrid Design Studiossupporting
confidence: 90%
See 1 more Smart Citation
“…This points perhaps to an emergent studio culture in which students are willing to engage more independently with lecture material and for this engagement to develop in the expanded context of individual circumstance rather than in the 'flattened' environment of the classroom. This finding is consistent with recent studies (Fleischmann, 2021) which have broadly indicated a preference for hybrid design studios that utilise a virtual educational environment to transcend the geographical constraints of the university and broaden possible inputs, and also integrate the specific FTF needs of studiobased education (Mironowicz & Schretzenmayr, 2020;Katsavounidou, 2022). The clear preference for FTF presentations and reviews from both students and tutors shows that at the critical momentsthat is in the scenarios that may have a tangible impact on student progression and potential employabilitythere's no substitute for FTF studio.…”
Section: The Inevitability Of Hybrid Design Studiossupporting
confidence: 90%
“…Or do we recognise that a shift has taken place, and that shift is so broad-ranging, so global, that a new normal has emerged that cannot now be supressed or regarded as a temporary shift in approach to teaching architectural design studio? As much as both tutors and students may wish to, we cannot un-know this new terrain becauseas our study and other recent studies show (Mironowicz & Schretzenmayr, 2020;Katsavounidou, 2022)student and staff expectations and capabilities have now shifted. We are not yet resigned to this shift, and we are evidently not too happy about it either, but a shift has taken place and to ignore it would simply reinforce the perceived fixedness of entrenched teaching cultures within architectural design studio culture.…”
Section: Best Of Both Worldsmentioning
confidence: 67%
“…Before the COVID-19 pandemic, online education was represented mostly by selflearning courses running in an asynchronous setting in order to reach a broader audience (Godschalk & Lacey, 2001;Lawhon, 2003). However, architecture and planning as disciplines are anchored in space; thus, virtual teaching platforms cannot easily recreate the studio atmosphere (Katsavounidou, 2022). Furthermore, the studio as a learning environment is interactive, participatory, and collaborative by nature.…”
Section: Digitalization Of Studio Educationmentioning
confidence: 99%
“…Thus, in pre-covid settings, studio courses were not commonly organized online (Pojani et al, 2018). However, the urgent need to organize teaching remotely in response to the outbreak of COVID-19 pandemic also affected architectural design and planning studios (Katsavounidou, 2022;Kim, 2022).…”
Section: Digitalization Of Studio Educationmentioning
confidence: 99%
See 1 more Smart Citation